A survey-based study identifies common but unrecognized symptoms in a large series of juvenile Huntington's disease. (October 2017) - Moser, Amelia D; Epping, Eric; Espe-Pfeifer, Patricia; Martin, Erin; Zhorne, Leah; Mathews, Katherine; Nance, Martha; Hudgell, Denise; Quarrell, Oliver; Nopoulos, Peg
Aim: The symptoms of Huntington's disease are well known, yet the symptoms of juvenile Huntington's disease (JHD) are less established due to its rarity. The study examined a cluster of symptoms considered to be common, but under-recognized in JHD: pain, itching, sleeping difficulties, psychosis and tics.Materials & methods: A symptom survey was constructed using the online tool Qualtrics and dispersed to JHD caregivers through websites.Results: A total of 33 surveys were completed. Disrupted sleep was the most prevalent symptom (87%), followed by tics (78%), pain (69%), itching (60%) and psychosis (39%).Conclusion: Despite limitations, the study supports that there are symptoms in the JHD population that are not considered classic, however, are common and significant for patients and caregivers.